2014
DOI: 10.1111/1471-0528.12909
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of exercise for the prevention and treatment of antenatal depression: systematic review with meta‐analysis

Abstract: Background Antenatal depression can have harmful consequences for the mother and fetus. Exercise may be a useful intervention to prevent and treat antenatal depression.Objectives This systematic review aims to establish whether there is sufficient evidence to conclude that exercise is an effective intervention for preventing and treating antenatal depression.Search strategy Searches using electronic databases from MEDLINE, Cochrane Library, CINAHL, EMBASE, AMED and PsycINFO were performed.Selection criteria Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 31 publications
(132 reference statements)
2
89
0
4
Order By: Relevance
“…Thirteen articles [1,9,[51][52][53][54][55][56][57][58][59][60][61] were included for systematic review and meta-analysis. All the included studies were prospective studies that examined the association between depression and obesity, of these, seven studies examined depression leading to obesity [1,9,51,52,54,55,57] and six studies investigated obesity leading to depression [53,56,[58][59][60][61]. Three of the studies presented the longitudinal bidirectional data [1,53,56].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen articles [1,9,[51][52][53][54][55][56][57][58][59][60][61] were included for systematic review and meta-analysis. All the included studies were prospective studies that examined the association between depression and obesity, of these, seven studies examined depression leading to obesity [1,9,51,52,54,55,57] and six studies investigated obesity leading to depression [53,56,[58][59][60][61]. Three of the studies presented the longitudinal bidirectional data [1,53,56].…”
Section: Resultsmentioning
confidence: 99%
“…Adult depression is persistent and commonly recurs across the life course [56,57]. After the first episode of depression, percentage estimates for further episodes do vary greatly and have been reported to range from 40% to 85%, depending upon the sample and measures used [58]. Clinical settings showed that the chronicity of depression varies from between 21% to 37% after one year, and between 60% and 75% after five years of follow-up; but these comprise the most severe, pervasive and recurrent cases [59][60][61].…”
Section: Prevalence and Burden Of Adult Depressionmentioning
confidence: 99%
See 3 more Smart Citations